Impact of anesthetic regimen on the respiratory pattern, EEG microstructure and sleep in the rat model of cholinergic Parkinson's disease neuropathology. (24th September 2015) - Lazic, K.; Petrovic, J.; Ciric, J.; Kalauzi, A.; Saponjic, J.
Highlights: We studied the impact of anesthesia in the rat model of cholinergic neuropathology. Anesthetic impact was followed by EEG, respiratory pattern, and sleep alterations. Ketamine/diazepam is adverse for EEG and respiratory pattern vs. pentobarbital. Ketamine/diazepam anesthesia abolished the NREM hallmarks of PPT lesion. Ketamine/diazepam anesthesia may be beneficial for post-anesthesia sleep. Abstract: Objectives: We hypothesized that the impact of distinct anesthetic regimens could be differently expressed during anesthesia and on post-anesthesia sleep in the neurodegenerative diseases. Therefore, we followed the impact of ketamine/diazepam and pentobarbital anesthesia in a rat model of the severe Parkinson's disease cholinergic neuropathology on the electroencephalographic (EEG) microstructure and respiratory pattern during anesthesia, and on the post-anesthesia sleep. Methods: We performed the experiments on adult, male, spontaneously breathing Wistar rats chronically instrumented for sleep recording. The bilateral pedunculopontine tegmental nucleus (PPT) lesion was done by ibotenic acid microinfusion. Following postoperative recovery, we recorded sleep for 6 h, induced anesthesia 24 h later using ketamine/diazepam or pentobarbital, and repeated sleep recordings sessions 48 h and 6 days later. During 20 min of each anesthesia we recorded both the EEG and respiratory movements. For sleep and EEG analysis, Fourier analysis was applied on 6-h recordings, and each 10-s epoch was differentiated as a state of wakefulness (Wake), non-rapid eye movement (NREM) or rapid eye movement (REM). Additionally, the group probability density distributions of all EEG frequency band relative amplitudes were calculated for each state, with particular attention during anesthesia. For respiratory pattern analysis we used Monotone Signal Segments Analysis. The PPT lesion was identified through nicotinamide adenine dinucleotide phosphate (NADPH) diaphorase histochemistry. Results and conclusions: Our data show that the ketamine/diazepam anesthetic regimen in the PPT-lesioned rats induces more alterations in the EEG microstructure and respiratory pattern than does the pentobarbital anesthesia. In addition, the equal time required to establish an anesthetized state, and the long-term effect on post-anesthesia sleep in the PPT-lesioned vs. control rats suggest this anesthetic regimen as potentially more beneficial both for anesthesia induction and for post-anesthesia sleep in the surgical procedures of the elderly, and Parkinson's, and Alzheimer's patients.